The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00420-018-1292-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site musculoskeletal pain in Swedish police: associations with discomfort from wearing mandatory equipment and prolonged sitting

Abstract: PurposeMusculoskeletal disorders are considered as a major issue affecting the health and well-being of active duty police. Discomfort from wearing mandatory equipment and sitting for long periods of time in fleet vehicles are workload factors linked to musculoskeletal disorders in police. This study aims to determine the prevalence of multi-site musculoskeletal pain among Swedish police and to explore the possible association to discomfort experience when wearing mandatory equipment and sitting for long perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 37 publications
(76 reference statements)
1
38
0
1
Order By: Relevance
“…The police are an occupational group known to have a high prevalence of musculoskeletal disorders, with lower back pain most frequently reported [14, 15]. In a recent Swedish study, lower back pain was reported by 43% of police as compared to 32% of the general working population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The police are an occupational group known to have a high prevalence of musculoskeletal disorders, with lower back pain most frequently reported [14, 15]. In a recent Swedish study, lower back pain was reported by 43% of police as compared to 32% of the general working population.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent Swedish study, lower back pain was reported by 43% of police as compared to 32% of the general working population. In addition, multi-site musculoskeletal pain was more frequently reported than single-site pain and found to be strongly associated with discomfort experienced from the use of mandatory equipment (duty belt and body armour) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Con respecto al dolor lumbar el 75,5% de policías presentan dolor lumbar. Esto concuerda con diversos reportes previos: Cardoso E (14) , Brown JJ (15) , Gruevski KM (16) . Este problema es frecuente y grave en el personal policial (17) .…”
Section: Discussionunclassified
“…The vest is bulky, stiff and secured tightly to the trunk with a system of Velcro-straps, and as such could plausibly impact the biomechanics of the upper body negatively. In addition, the added weight has been reported to result in limited mobility and can cause significant discomfort [ 1 , 2 , 3 , 4 , 5 , 6 ]. The mass of the ballistic vest worn by the Danish police officers ranges 3.5–8.5 kg depending on the units the officers are assigned to.…”
Section: Introductionmentioning
confidence: 99%